Menulis Permulaan dan Media Reglet: Penelitian Tindakan pada Siswa Tunanetra - Ika Asrianti Puspitasari; Anas (DIALEKTIKA: Jurnal Ilmiah Pendidikan Bahasa, Sastra, dan Matematika, 2022)
The current paper investigates the application of Reglet media in early writing for 7th graders of SLB Adiguna. It examines the writing performance improvement using Reglet Media for 7th graders at one of an exceptional school. This classroom action research was carried out at SLB Adiguna. The data of this study were the teaching-learning process and the students’ writing performance which were collected using teacher-student activity observation sheets and writing test instruments. The students’ performance in writing was improved using Reglet media. The pre-test and cycle I scores which were 62 had improved to 80 in cycle II. On the other hand, the teacher activities showed improvement by using reglet media in the teaching of writing letters, words, and simple sentences. It was 62.53% in first cycle then was increased to 88.45% at cycle II. In addition, the results of student activities also improved from 71.42% in first cycle to 92.85% in cycle II. In conclusion, the use of reglet media can improve the students’ performance in beginning writing especially SLB Adiguna 7th Graders.